Specific Financial Accounting Standards for Political Parties (The Comparison of PSAK 45 and the Law of Political Parties in Indonesia) - Januri Januri; Riva Ubar Harahap; Muhammad Fahmi (Budapest International Research and Critics University, 2022)
This research deals to reveal whether the existing PSAK 45 can be used as a financial accounting standard for political parties and whether a specific financial accounting standard for political parties is needed to replace the existing PSAK 45. This is a qualitative research through literature study with comparative data analysis method, the standards made by IAI; namely PSAK 45 Financial Reporting of Non-Profit Entities is compared to the laws of political parties, especially those related to financial reporting. The results provide that PSAK 45 cannot be used as a standard for financial reporting for political parties. So that a specific financial accounting standard for political parties is needed to replace the existing PSAK 45.